2019
DOI: 10.31234/osf.io/3xwnd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How multidisciplinary are multidisciplinary case reviews in cancer care? Feasibility analysis of a theory-driven team decision-making fidelity framework

Abstract: Background Multidisciplinary teams (MDTs) are a standard cancer care policy in many countries worldwide. Despite an increase in research in a recent decade on MDTs and their care planning meetings, the implementation of MDT-driven decision-making (fidelity) remains unstudied. We report a feasibility evaluation of a novel method for assessing cancer MDT decision-making fidelity. We used an observational protocol to assess (1) the degree to which MDTs adhere to the stages of group decision-making as per the ‘Ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This might explain divergent results concerning the need for MTCpp: While Massoubre et al 36 found that 97% of MTC recommendations without patient participation were followed and concluded that MTCpp is not essential, Hollunder et al found a great lack of MTC decision adherence caused by missing patient information and failure to consider their preferences 23 which might increase the need for MTCpp, even in the case of limited clinical evidence 53 or limited multidisciplinary discussion. 54,55 For future research, this should firstly mean that patient outcomes have to be analyzed as they are an important part of general MTC outcome quality. 49,50,[56][57][58][59] Some patient outcomes will be analyzed in the quantitative part of the PINTU study.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain divergent results concerning the need for MTCpp: While Massoubre et al 36 found that 97% of MTC recommendations without patient participation were followed and concluded that MTCpp is not essential, Hollunder et al found a great lack of MTC decision adherence caused by missing patient information and failure to consider their preferences 23 which might increase the need for MTCpp, even in the case of limited clinical evidence 53 or limited multidisciplinary discussion. 54,55 For future research, this should firstly mean that patient outcomes have to be analyzed as they are an important part of general MTC outcome quality. 49,50,[56][57][58][59] Some patient outcomes will be analyzed in the quantitative part of the PINTU study.…”
Section: Discussionmentioning
confidence: 99%